Value Chain Development Model for Livestock Downstreaming in Indonesia: Model Pengembangan Rantai Nilai Dalam Hilirisasi Peternakan di Indonesia - Azis, Arif Rahman; Hamka, Muhammad Subhan; Bilyaro, Woki; Dani, Muhammad; Saputri, Kade Wahyu (Buletin Peternakan Tropis, 2025)
Value chain development models in livestock downstreaming are crucial for enhancing the competitiveness of the national livestock sector. This article aims to analyze various value chain development models that support the downstreaming of livestock in Indonesia. The methodology employed is a comprehensive literature review of current research on value chains and livestock downstreaming. The findings indicate that the success of value chain development relies on the integration of business actors, the adoption of technology and innovation, the development of supporting infrastructure, and the harmonization of policies. Implementing downstreaming through the establishment of processing industries has positively impacted the added value of livestock products. The proposed value chain development model emphasizes the need for triple helix collaboration among the government, the private sector, and academia. Additionally, it must be tailored to the specific characteristics and potential of each region. In conclusion, this study highlights the significance of an integrated approach to developing livestock value chains to create a sustainable and competitive ecosystem in the livestock sector.